Financial Crisis, Bad Debt and Uncollectible Receivables: Evidence from UAE - Nizar Mohammad Alsharari; Rasha Abousamra (Universitas Trisakti, 2018)
This study aims to study the methods used in accounting for calculating bad debts in a financial setting and comparing it with the debt collection methods in an academic environment in UAE especially in Abu Dhabi University. It also focuses on exploring the reasons behind defaulting payments in an academic setting and finally recommending a sample policy for debt collection an academic environment has been demonstrated. It is clearly that the non-performing loans prevailing in the UAE could be twofold in the coming years due to a constant surge in the credit demand, and the banks as well as financial institutions cannot agree on debt collection policies. The position of UAE in context is still better than many other countries. However, this will negatively affect the financial positions of the organizations if proper policies are not in place for the debt collection procedures. The credit demand is going to increase as more and more people are keen on investing in the real estate sector of the country and prefer taking long term mortgages to finance their dream houses. It must be noted that UAE’s overall receivables was stated as AED 28.2 billion in 2012, which then increased to AED 35.3 billion in 2013, again indicating the surge in demand for credit and the corresponding impact on increase in bad debts. This study concludes that a number of resources were available when it comes to collecting bad debts in banking or financial environment, but collecting bad debts in higher educational institutions was very limited, in the context of UAE